Autobiographical Narrative and Intercultural Awareness - Daniela Cuccurullo (Je-LKS: Journal of E-Learning and Knowledge Society, 2019)
The currency of intercultural education has risen worldwide in response to increased diversity within societies resulting from migration and global flows of populations. As intercultural education becomes a core responsibility of schooling, the attention to developing students’ intercultural capabilities grows even faster. The school and all the educational agencies must find the most suitable tools to adequately address the complex multiculturalism of the third millennium, so to promote the students’ ability to understand one another across and beyond all types of cultural barriers. This paper offers a reflexive analysis of the efficacy of using autobiographical narratives for enhancing students’ intercultural awareness. Autobiographical narratives have a productive potential as a strategy for stimulating reflexivity about cultural identities and intercultural relations. The Autobiography of Intercultural Encounters (AIE), published by the Council of Europe (2009), is proposed and analyzed as a framework that can help students reflect critically on specific intercultural encounters and promote intercultural communication situations. ‘Intercultural communication’ is today a model that allows all children and young people to recognize and being aware of each other’s identity, as it is oriented towards fostering interaction, dialogue, mutual recognition and enrichment of any individual, in respect of the different identities of the other; it is an approach that offers a forward-looking model for managing cultural and language diversity.